External Costs of Road, Rail and Air Transport - a Bottom-Up Approach - Sigurd Weinreich; Klaus Rennings; Barbara Schlomann; Christian Geßner; Thomas Engel (Zentrum für Europäische Wirtschaftsforschung (ZEW), 1998)
This paper aims to describe the calculation of environmental and health externalities caused by air pollutants, accidents and noise from different transport modes (road, rail, air) on the route Frankfurt-Milan. The investigation is part of the QUITS project (QUITS = Quality Indicators for Transport Systems), commissioned by the European Commission DG VII. The evaluation of the external costs is based on a bottom-up approach. The calculation involves four stages: emissions, dispersion, impacts, and costs, following the impact pathway approach. An integrated model for the valuation of environmental and health costs due to air pollutants will be presented consisting of three computer programmes which are linked together. For passenger road traffic, total external costs amount to about 44 ECU/1000 pkm on the route Frankfurt -Milan, including the impact categories air pollutants (15.6), global warming (5.2), noise (3.8), and accidents (19.6 ECU/1000 pkm). Concerning a comparison of the transport modes, external costs of passenger road traffic are about 9 times as high as those of rail traffic and about twice as high as those of air traffic. For goods transport by road, the total external costs (30.6 ECU/1000 tkm) are about 11 times as high as those of rail traffic.
Keywords: 330; external costs; transport systems; environmental impacts; bottom-up approach; Verkehrsökologie; Verkehrsweg; Externer Effekt; Soziale Kosten; Schätzung; Deutschland; Schweiz; Italien